Estimation for Minimum Reinforcement Requirements Length in Large Diameter Bored Piles with Statistical Analyses of Finite Element Method Resulting - Taweechai, Noppharit; Li Jingye (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 30, 2025)
The purpose of this article is to present the estimation of reinforcement requirement length in large diameter bored piles with statistical results of design with finite element analysis. This study case has been recorded of 4,822 bored piles with dimeter of 1.0, 1.2, 1.5, and 2.0 m. in Thai-Chinese high-speed rail project, contract 4-3: Nava Nakorn to Ban Po, Ayutthaya, Thailand. A practical procedure for defining of reinforcement length in piles has been simulated by pile-soil models under the independent variables of geological drilling and interpretation in engineering properties of soil including pile’s properties to compute model with finite element method. The results of finite element analysis have been observed with principle of behavior of long elastic pile to define an effective length due to lateral load condition. The statistical analysis of effective length results in all of bored piles is minimum reinforcement length with 39 percentage of bored pile length. All purposes and recommendations are presented which intend to be used a reliability of finite element analysis together with accumulated its resulting data to obtain final estimation of bore piles with minimum reinforcement case.